P133 "Not only but also" Establishing a first point of contact and triage service. (1st October 2013) - O'Grady, Jackie; Cottingham, Laura; Linehan, Gail
Abstract : Background: A South West London Hospice receiving around 900 referrals per year. First Point of Contact (FPC) service was established following identification of variation in response times for initial contact to arrange assessment. In collaboration, a Triage service provides immediate access to a Clinical Nurse Specialist (CNS) for advice, support and responsive emergency visits. Aims: To provide an efficient, responsive referral service. To provide accessible telephone support for patients, relatives and professionals Provision of a responsive approach to requests for urgent home visits. Service configuration: A team of three CNSs (WTE 2.2) covering 08:30-18:00 Monday-Friday. Referrals reviewed on receipt with responsive contact Urgent referrals initiate immediate FPC contact to assess and where necessary a same day visit by the triage CNS. Routine referrals assessed by telephone within 48 hours with first visit arranged within two weeks FPC attends weekly Palliative Care MDT meetings at both local hospitals The triage CNS offers telephone 'help line' advice and support to referred service users and professionals. Outcomes: Three month pilot (17 th December - 17 th March 2013) compared to November 2012 demonstrated: 70% improvement in response times to all referrals being contacted within 24hrs 94% of urgent referrals contacted within 24 hours 21% improvement in 2 week first visit 76% of received calls completed by Triage CNS supporting the community team. A result of service questionnaire from relevant stakeholders is awaited. Implication to delivery of specialist palliative care: Better end of life management within the community through advice given to GPs at point of referral e.g. ensuring appropriate documentation and medications in place Improved access to the hospice for referrals and advice Improved response to referrals Improved communication, collaborative working and outcomes for patients.